Preference for timber as a building material-a survey of homeowners in Bachok, Kelantan - Mohamed, Shukri; Yaakob, Sam Shor Nahar; Abdul A'zim, Amir A'ffan; Abdul Manaf, Nurul Najihah; Hisamuddin, Siti Hajar; Ab Aziz, Nur Aiman Shuhada (Forestry Department Peninsular Malaysia, 2018)
Besides the construction industry, there are also private individuals who are involved in the construction of buildings especially residential building in the country. While the construction industry in Malaysia may not be keen in using timber and timber products, these individual homeowners would to a large extent have a choice of selecting the materials used in the construction of their residential units. A self-administered questionnaire was distributed to 496 homeowners aimed at determining their preference for timber as a building material for residential buildings. In general, the respondents have a positive attitude towards timber as a building material, but they are concerned of its price and availability, as well as its susceptibility to pest attacks. Only about a quarter of the respondents, and even among owners of timber houses, preferred timber as a building material. The main reasons for their choice are that timber houses are unique and comfortable. Durability, low price and availability of skilled labour are the reasons for most of the respondents to choose alternative building materials.